Technology Impact on Construction Productivity: Remodelling the Indian Construction Industry - Talapaneni, Murali Naidu (Digital Repository of Theses, 2025)
The construction industry, characterized by its intricate processes and inherent challenges, has undergone substantial transformation with the advent of technology. This doctoral thesis examines the impact of technological advancements on construction productivity, focusing on how these innovations enhance efficiency, reduce costs, and improve project outcomes. Employing a mixed-methods approach, the research integrates quantitative data analysis with qualitative insights to provide a holistic understanding of technology's influence on construction productivity. Through the analysis of case studies, industry reports, and empirical data, the study identifies key technological innovations—such as Building Information Modeling (BIM), automation, artificial intelligence (AI), and Internet of Things (IoT) applications—as pivotal drivers of productivity improvements in the construction sector. The findings demonstrate that these technologies significantly enhance project planning, realtime decision-making, resource allocation, and quality control. BIM emerges as a transformative tool, streamlining design and construction processes, reducing errors, and facilitating improved stakeholder communication. Automation technologies, including robotics and prefabrication, accelerate construction tasks, lower labor costs, and mitigate onsite risks. AI and IoT are revolutionizing construction sites by enabling predictive maintenance, enhancing safety protocols, and optimizing material usage, collectively fostering a more efficient and sustainable construction workflow. The study also delves into the theoretical implications, positioning technology as a crucial element in the evolution of construction methodologies. It advocates for a paradigm shift towards agile, data-driven, and responsive project management practices, emphasizing the integration of digital tools with strategic management to propel industry growth. By bridging the gap between technological innovations and practical applications, the research enriches academic understanding of the factors influencing construction productivity. From a managerial perspective, the study offers actionable recommendations for construction firms on effectively integrating technology into operations. It underscores the importance of investing in workforce training and development to harness these new tools and fostering a culture of innovation. Despite its comprehensive approach, the study acknowledges limitations, such as data collection challenges and variability in technological adoption rates. These suggest a need for future research focusing on region-specific case studies and the long-term effects of technology on productivity. Ultimately, this study underscores the transformative potential of technology in construction, setting the stage for further academic exploration and industry dialogue to maximize technological investments for sustainable growth and efficiency. Keywords: Construction Industry, Technology Integration, Construction Productivity, Building Information Modeling (BIM), Automation, Artificial Intelligence (AI), Internet of Things (IoT), Efficiency, Cost Reduction.